Optimization of Carbon Dioxide Reduction in Biohythane Using an Innovative Water Scrubber - S Chuayboon; P Danugviluilux; S Prasertsan; P Prasertsan (My University, 2019)
The major problem of biohythane production from palm oil mill effluent is the high carbon dioxide (CO2) content. In this study, an innovative water scrubber system for upgrading biohythane has been experimentally investigated. Biohythane composing of ∼53.34% of CH4, ∼39.12% of CO2, and ∼7.54% of H2 was simulated regarding the composition of biohythane in the lab scale. Response surface methodology (RSM); a 5-level, 3-factor, central composite design (CCD), was employed to optimize three important parameters (biohythane flow-rate, water flow-rate, and operating time) in order to minimize the CO2 content in the biohythane production. As a result, CO2 concentration decreased with the increase of both the operating time and water flow-rate but inversely proportion to the biohythane flow-rate, which led to higher CO2 absorption by water. The optimal condition regarding the maximum value of CO2 reduction was found at: 3 Nl/min of biohythane flow-rate, 16 Nl/min of water flow-rate, and 9 min of operating time, thereby yielding 77.6% of CO2 reduction.
Keywords: Carbon Dioxide Capture Technologies